BRCA1 regulates HMGA2 levels in the Swan71 trophoblast cell line. Issue 11 (13th August 2019) - West, Rachel C.; Russ, Jennifer E.; Bouma, Gerrit J.; Winger, Quinton A.
Abstract: During early placental development, tumor suppressors and oncogenes work synergistically to regulate cell proliferation and differentiation in a restrained manner compared with the uncontrollable growth in cancer. One example of this partnership is the regulation of the oncofetal protein HMGA2 by BRCA1. BRCA1 forms a repressor complex with ZNF350 and CtIP to bind to the promoter of HMGA2, preventing transcription. Chromatin immunoprecipitation determined BRCA1 forms this repressor complex in human trophoblast cells, suggesting a role in the placenta. Furthermore, miR‐182 has been shown to target BRCA1 mRNA in ovarian cancer cells, blocking the formation of the BRCA1 repressor complex and allowing increased transcription of HMGA2. miR‐182 was one of the first miRNAs described as elevated in the serum and placentas of preeclamptic women. Therefore, we hypothesized that BRCA1 is essential for normal trophoblast cell development. We used CRISPR‐Cas9 genome editing and miR‐182 overexpression to decrease BRCA1 protein in the Swan71 cell line. HMGA2 was significantly increased in the BRCA1 KO and miR‐182 overexpressing cells compared to controls. We also determined that BRCA1 repressor complex binding to HMGA2 was significantly reduced in BRCA1 KO and miR‐182 overexpressing cells compared with controls, leading us to conclude that increased HMGA2 was because of decreased binding of the BRCA1 repressor complex. Finally, we found that the caspase activity was significantly higher in BRCA1 KO and miR‐182 overexpressing cells suggesting an increased amount of apoptosis. These data suggest that BRCA1 is an important regulator of the oncofetal protein HMGA2 and promotes cell survival in human placental cells. Abstract : BRCA1 forms a repressor complex with ZNF350 and CtIP that binds to the promoter regions of several oncogenes to prevent transcription. In the placenta, we found that this repressor complex binds to the promoter of HMGA2. Upon knocking out BRCA1, this repressor complex no longer bound to HMGA2's promoter, allowing for increased transcription and increased genomic instability.